Pelatihan Penyusunan Laporan Keuangan Gereja GBKP sesuai ISAK 335: Pendekatan Metode Diskusi Interaktif dan Demonstrasi - Ita Salsalina Lingga; Joni Joni; Tan Ming Kuang; Lauw Tjun Tjun; Elyzabet Indrawati Marpaung; Candra Sinuraya; Maria Natalia; Sinta Setiana; Endah Purnama Sari Eddy; Ollin Flajuanta Tjando; Vania Marleen; Keith Yohanes Reinhart (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Nonprofit organizations such as churches have a moral and institutional obligation to manage their finances transparently and accountably to their entire congregation. However, many churches face limited human resource capacity in accounting and financial reporting. Maranatha Christian University, in collaboration with the Batak Karo Protestant Church, held a community service activity aimed at improving the accounting literacy of GBKP administrators through a training approach on preparing church financial reports in accordance with ISAK 335 based on interactive discussion method and live demonstrations. A total of 18 participants were involved in their program. An evaluation instrument in the form of a comprehension test was administered before and after the training to quantitatively measure the program’s effectiveness. The data obtained showed a significant improvement in understanding (94%) of participants after participating in the training series. The live demonstration approach was deemed capable of simplifying technical accounting concepts to make them more easily understood by participants with non-accounting backgrounds. These findings confirm that improving the understanding of accounting concepts and the ability to prepare financial reports for church communities depends heaviliy on the selection of appropriate and contextual delivery methods. This program is expexted to become a reference model for nonprofit organizations.